Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/hep.31487
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Liver Tests in COVID‐19: A Retrospective Observational Cohort Study of 1,827 Patients in a Major U.S. Hospital Network

Abstract: BaCKgRoUND aND aIMS: The coronavirus-19 disease (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 virus, is associated with significant morbidity and mortality attributable to pneumonia, acute respiratory distress syndrome, and multiorgan failure. Liver injury has been reported as a nonpulmonary manifestation of COVID-19, but characterization of liver test abnormalities and their association with clinical outcomes is incomplete. appRoaCH aND ReSUltS: We conducted a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
243
0
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(301 citation statements)
references
References 31 publications
31
243
0
7
Order By: Relevance
“…in 29 July 2020 reported that abnormal liver tests were commonly observed in hospitalised patients with COVID-19, both at admission (AST 66.9%, ALT 41.6%) and peak hospitalisation (AST 83.4%, ALT 61.6%) [35]. In addition, multivariate analysis revealed an association between abnormal liver tests and severe COVID-19, including ICU admission, mechanical ventilation and death, which suggested that abnormal liver tests may be associated with poorer clinical outcomes, which suggested that abnormal liver tests may be associated with poorer clinical outcomes [35]. These data further demonstrated the predictive value of elevated concentrations of ALT and AST in the progression and prognosis, as well as the ‘recurrence’ of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…in 29 July 2020 reported that abnormal liver tests were commonly observed in hospitalised patients with COVID-19, both at admission (AST 66.9%, ALT 41.6%) and peak hospitalisation (AST 83.4%, ALT 61.6%) [35]. In addition, multivariate analysis revealed an association between abnormal liver tests and severe COVID-19, including ICU admission, mechanical ventilation and death, which suggested that abnormal liver tests may be associated with poorer clinical outcomes, which suggested that abnormal liver tests may be associated with poorer clinical outcomes [35]. These data further demonstrated the predictive value of elevated concentrations of ALT and AST in the progression and prognosis, as well as the ‘recurrence’ of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the majority of cases, SARS‐CoV‐2 associated liver injury was generally mild and did not exceed >5 times the upper reference limit, therefore not fulfilling the diagnostic criteria for hypoxic hepaitis 35 . These findings were also obtained in critically ill patients referred to the ICU, suggesting that even in cases of severe respiratory failure during SARS‐CoV‐2 infection, the adequate oxygen supply to the liver is ensured by compensatory mechanisms 35,36,39,149‐154 …”
Section: Sars‐cov‐2 and Hypoxic Hepatitismentioning
confidence: 93%
“…35 These findings were also obtained in critically ill patients referred to the ICU, suggesting that even in cases of severe respiratory failure during SARS-CoV-2 infection, the adequate oxygen supply to the liver is ensured by compensatory mechanisms. 35,36,39,[149][150][151][152][153][154] of DILI associated with tocilizumab use in a COVID-19 patient has been reported. 62 Tocilizumab undergoes minimal hepatic metabolism, and the most probable etiology for its hepatotoxic effect is the interference with the IL-6 pathway, which plays a key role in hepatic regeneration.…”
Section: Sar S -Cov-2 and Hyp Oxi C Hepatitismentioning
confidence: 99%
“…According to these data, patients with abnormal AST at admission have a higher risk of mechanical ventilation (OR 3.09, P < 0.001), as are those with abnormal AST, ALT and ALP at peak hospitalization 15 Overall, data support a modest cytopathic acute liver damage by SARS-CoV-2 through a direct cytopathic effect, due to infection of hepatocytes mediated by the highly expressed ACE2 receptors.…”
Section: Doe S Sar S -Cov-infec Ti On C Aus E Damag E To a He Althymentioning
confidence: 85%